Erica Iop 5A: Mesoscale Structure and Frontal Evolution. - Lane, Timothy G. (1996)
A mesoscale investigation was conducted on the rapid coastal cyclogenesis that occurred during Intensive Observation Period (IOP 5A) of the Experiment on Rapidly Intensifying Cyclones over the Atlantic (ERICA). Forecasts from a double-nested version of the Navy Operational Regional Analysis and Prediction System (NORAPS) and Multiquadric Interpolation (MQI) objective analyses utilizing operationally available and some special ERICA data were examined to study the mesoscale structure and frontal evolution associated with this explosively deepening coastal cyclone. Additionally, the ability of NORAPS to accurately simulate the explosive cyclogenesis was investigated. The frontal evolution showed characteristics of a classical occlusion, similar to the Norwegian cyclone model, and marine frontal structure as described by Shapiro and Keyser (1990). The frontal evolution was highly influenced by the prior existence of strong Arctic and coastal fronts. These fronts intensified during the course of the storm development and did not develop as a result of the cyclogenesis. The NORAPS model forecasts were compared against satellite imagery, surface observations, MQI analyses, and observed soundings taken during the ERICA study. The double-nested version of NORAPS was found to be an excellent tool for forecasting the mesoscale frontal structure and intensity of this explosively deepening coastal cyclone.